Cloud computing and big data : second International Conference, CloudCom-Asia 2015, Huangshan, China, June 17-19, 2015, Revised selected papers /: second International Conference, CloudCom-Asia 2015, Huangshan, China, June 17-19, 2015, Revised selected papers. (2015) - Unknown
No abstract available